Leftover medicine among patients with non-communicable diseases in the community of Phayao province: prevalence, quantity, value, and the associated factors - Wuttikul, Chanadda; Phattanasobhon, Sirayut; Suksab, Thitaphon; Laohaphongsomboon, Phonpawi; Ruangsuwan, Maneekarn; Sookying, Sontaya (Health Science, Science and Technology Reviews, 2025)
Leftover medicines among patients with non-communicable diseases (NCDs) are an important issue affecting Thailand’s public health system. This study aims to investigate the prevalence, quantity, value, and associated factors of leftover medicines among patients with NCDs in a community setting in Phayao Province. A cross-sectional observational study was conducted through home visits. Data was collected via structured interviews and analyzed using descriptive statistics and multivariable logistic regression. Among 361 participants, 89.8% had at least one item of leftover medicine, with a median of two items per person. The total amount of leftover pills was 21,534, with an estimated value of 18,340.4 baht. Amlodipine 5 mg has the highest quantity and value of leftover medication. The leading causes of leftover medicines were forgetting to take medications (55.6%) and receiving medicine exceeding the appointment interval (52.5%). Factors significantly associated with having leftover medicines for more than eight weeks included having multiple chronic conditions (adjusted odds ratio [aOR] 1.51; 95% confidence interval [CI]: 1.06–2.13), use of herbal or dietary supplements within the past six months (aOR 2.33; 95%CI: 1.01–5.34), and incorrect medication use (aOR 9.87; 95%CI: 2.37–41.04). While most patients practiced appropriate medicine management, such as returning leftover medicine to healthcare facilities, some exhibited risky behaviors, including sharing medicines with others and improper disposal. The findings highlight that multiple comorbidities, herbal product use, and non-compliance are key contributors to leftover medicine among patients with NCDs. Developing a screening system for at-risk patients, promoting medication adherence, establishing appropriate prescribing practices, and educating the public on proper medicine management are essential strategies to reduce the burden of leftover medicine and its negative impact on healthcare systems, economic resources, and the environment.